A systematic review of proteomic biomarkers associated with risk stratification in pediatric acute lymphoblastic leukemia - Dehghan-Nayeri, Nasrin; Eshghi, PeymanÂ; Goudarzi Pour, KouroshÂ; Gharehbaghian, Ahmad (Archives of Advances in Biosciences, 2018)
Risk-based therapy protocols have dramatically improved survival rates in more than 80% of childhood acute lymphoblastic leukemia (chALL). Prognostic biomarkers could be valuable for predicting the relapsed ALL patients and may therefore contribute to improving ALL outcome. Presently, there are little data on the role of prognostic biomarkers in the risk stratification of ALL. The aim of the present systematic review is to survey the identified prognostic biomarkers of chALL. In this study, protein-protein interaction of identified biomarkers was evaluated to reveal the biological pathways related to high risk chALL. To pursue this goal, firstly all relevant studies were collected through the PubMed and Google Scholar databases with no restrictions. Then, the biomarkers of high risk patients were recorded and finally protein-protein interaction of biomarkers was analyzed through using the STRING database. After screening 82 abstracts, three studies were included with 36 high risk and 33 low risk B-ALL participants. Totally, 142 biomarkers were investigated in this study. Protein interaction network analysis of biomarkers revealed two main pathways, namely ribosome and spliceosome. Dysregulation of two key pathways, ribosome and spliceosome can be associated with the high risk phenotype of childhood acute lymphoblastic leukemia.